2014
DOI: 10.1142/s175882511450063x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transverse Shear and Normal Strains on Fg Plates Resting on Elastic Foundations Under Hygro-Thermo-Mechanical Loading

Abstract: The influence of temperature and moisture on the bending behavior of composite functionally graded material (FGM) plates resting on elastic foundations is investigated. A transverse shear and normal deformation theory are used with five unknown functions as opposed to six or even greater numbers in the case of other shear and normal deformation theories. An accurate solution is presented in the hygrothermal response of the FG plate with simply-supported edges and resting on elastic foundations. The interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Zidi et al [4] analyzed static responses of FG plates under hygro-thermo-mechanical loading using a four variable refined plate theory. Zenkour et al [5,6] investigated hygro-thermo-mechanical effects on behaviours of FG plates on elastic foundations. Fazzolari and Carrera [7] studied thermal stability of FG sandwich plates under various through-the-thickness temperature distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Zidi et al [4] analyzed static responses of FG plates under hygro-thermo-mechanical loading using a four variable refined plate theory. Zenkour et al [5,6] investigated hygro-thermo-mechanical effects on behaviours of FG plates on elastic foundations. Fazzolari and Carrera [7] studied thermal stability of FG sandwich plates under various through-the-thickness temperature distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Zenkour and Alghamdi [29] studied the bending response of nonsymmetric FGM sandwich plates in the thermal environment. In the hygrothermal environment, the bending analysis of FGM plates resting on elastic foundations is investigated by Zenkour et al [30]. Also, Zenkour et al [31] discussed bending analysis of laminated composite plates resting on Winkler-Pasternak foundations in a hygrothermal environment.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies about elastic or viscoelastic foundations can be found in the literature. [42][43][44][45][46][47][48][49][50][51] In this article, bending, buckling, and vibration behaviors of viscoelastic FG curved nanobeam embedded in an elastic medium are investigated based on nonlocal strain gradient theory. For the viscoelastic FG curved nanobeam, the material properties are graded in radial direction using two power-law forms.…”
Section: Introductionmentioning
confidence: 99%